2021
DOI: 10.1002/pbc.29184
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of children with acute lymphoblastic leukemia in Cambodia

Abstract: We report a retrospective analysis of 110 unselected pediatric patients with acute lymphoblastic leukemia (ALL) treated during 2015–2017 in a charity‐funded public institution in Cambodia with a reduced intensity ALL‐Moscow Berlin (MB)‐91 protocol. No patient abandoned treatment. Sixty‐three patients (57%) were high risk (HR). Seventy‐two patients (65.5%) reached complete remission (CR) on day 36. The 3‐year event‐free survival (EFS) and overall survival (OS) was 34.9% (50.5% for standard risk [SR]). Most deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The update of the AHOPCA 2008 study documented a 5‐year EFS rate of 47.4% ± 1.2% and an OS rate of 57.3% ± 1.2%, including abandonment as an event, and rates of 53.8% ± 1.3% and 61.6% ± 1.2%, respectively, when censoring treatment abandonment (Figure 1). These results are similar to those reported from Guatemala and other LMICs 9–12 …”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…The update of the AHOPCA 2008 study documented a 5‐year EFS rate of 47.4% ± 1.2% and an OS rate of 57.3% ± 1.2%, including abandonment as an event, and rates of 53.8% ± 1.3% and 61.6% ± 1.2%, respectively, when censoring treatment abandonment (Figure 1). These results are similar to those reported from Guatemala and other LMICs 9–12 …”
Section: Introductionsupporting
confidence: 91%
“…Delayed diagnosis, malnutrition, insufficient supportive therapy, abandonment of treatment, chemotherapeutic drug shortage, poor treatment adherence, and genetic polymorphism variations may all play a role in a poor prognosis 3–7 . However, numerous efforts have been made to improve the prognosis of ALL in LMICs 2,8–12 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the outset, the declared goal was to avoid drugs that cause unnecessary toxicity, severe and long‐lasting BM aplasia, and undesirable late effects. The protocol contains only moderate‐dose anthracyclines, no etoposide, no cyclophosphamide, and neither high‐dose ARA‐C nor high‐dose MTX 36 . Compared to a contemporary BFM study, toxicity was shown to be significantly lower with similar results 19,35 …”
Section: Discussionmentioning
confidence: 89%